2021
DOI: 10.1016/s1556-0864(21)01845-1
|View full text |Cite
|
Sign up to set email alerts
|

3P AZ12756122, a novel fatty acid synthase (FASN) inhibitor, reduces resistance properties in gefitinib- and osimertinib-resistant EGFR-mutated non-small cell lung cancer models

Abstract: months (p = 0,013). There were no significant differences in age, ECOG PS, histology, size, therapies or treatment line. Conclusions: The NLR remains a prognostic factor in both diseases, with or without EGFR mutation, but appear to have less impact on the outcome of EGFR mutated patients. In NSCLC EGFR mutated maybe inflammatory index could have implications on therapeutic choice, especially subsequent lines and his role deserves further study. Legal entity responsible for the study: Mario Scartozzi. Funding:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dichloroacetate PDHK inhibitor Induction of Acetyl-CoA formation [26] Atorvastatin CAV-1/GLUT-3 inhibitor Inhibition of glucose uptake and cholesterol synthesis [30] PF-429242 SREBP1 inhibitor Inhibition of lipid synthesis [31] Orlistat FASN inhibitor Inhibition of EGFR palmitoylation [32] Epalrestat AKR1B1 inhibitor Inhibition of GSH synthesis [33] PiperlongumineAuranofin ROS inducing agent Induction of oxidative stress [34] Buthionine sulfoximine GSH synthesis inhibitor Inhibition of GSH synthesis [34] 1,25D VDR agonist Inhibition of stemness phenotype [35] AZ12756122 FASN inhibitor Inhibition of stemness phenotype [36] Abbreviations: PDHK, pyruvate dehydrogenase kinase; Acetyl-CoA, acetyl coenzyme A; CAV-1, caveolin-1; GLUT-3, glucose transporter-3; FASN, fatty acid synthase; EGFR, epidermal growth factor receptor; SREBP1, sterol regulatory-element-binding protein 1; AKR1B1, aldo-keto reductase family 1 member B1; GSH, glutathione; ROS, reactive oxygen species; 1,25D, 1,25-dihydroxyvitamin D3; VDR, vitamin D receptor.…”
Section: Mechanism Of Action Downstream Effect Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Dichloroacetate PDHK inhibitor Induction of Acetyl-CoA formation [26] Atorvastatin CAV-1/GLUT-3 inhibitor Inhibition of glucose uptake and cholesterol synthesis [30] PF-429242 SREBP1 inhibitor Inhibition of lipid synthesis [31] Orlistat FASN inhibitor Inhibition of EGFR palmitoylation [32] Epalrestat AKR1B1 inhibitor Inhibition of GSH synthesis [33] PiperlongumineAuranofin ROS inducing agent Induction of oxidative stress [34] Buthionine sulfoximine GSH synthesis inhibitor Inhibition of GSH synthesis [34] 1,25D VDR agonist Inhibition of stemness phenotype [35] AZ12756122 FASN inhibitor Inhibition of stemness phenotype [36] Abbreviations: PDHK, pyruvate dehydrogenase kinase; Acetyl-CoA, acetyl coenzyme A; CAV-1, caveolin-1; GLUT-3, glucose transporter-3; FASN, fatty acid synthase; EGFR, epidermal growth factor receptor; SREBP1, sterol regulatory-element-binding protein 1; AKR1B1, aldo-keto reductase family 1 member B1; GSH, glutathione; ROS, reactive oxygen species; 1,25D, 1,25-dihydroxyvitamin D3; VDR, vitamin D receptor.…”
Section: Mechanism Of Action Downstream Effect Referencementioning
confidence: 99%
“…Collectively, impairing stem-like characteristics in EGFR TKI-resistant cells, as in this case by activating the 1,25D/VDR axis, led to resistance mitigation [ 35 ]. Moreover, preliminary findings suggested that a combination of osimertinib with a novel FASN inhibitor, AZ12756122, presented a synergistic effect overcoming osimertinib resistance in PC9 cells, likely by attenuating cancer stem cell features [ 36 ].…”
Section: Egfr Tki Resistance and Metabolism-mediated Stemnessmentioning
confidence: 99%